Gastric microbiota in a low- helicobacter pylori prevalence general population and their associations with gastric lesions - Ndegwa, Nelson; Ploner, Alexander; Andersson, Anders F.; Zagai, Ulrika; Andreasson, Anna; Vieth, Michael; Talley, Nicholas J.; Agreus, Lars; Ye, Weimin (Clinical and Translational Gastroenterology, 2020)
INTRODUCTION:Non-Helicobacter pylori microbiota might account for some cases with unexplained chronic gastritis that may in a minority eventually progress to gastric cancer through the Correa cascade. We characterized gastric microbiota by describing the normal stomach, compared it with early precancerous lesions and other disease states, and assessed whether H. pylori status affects bacterial diversity.METHODS:In a population-based study of those with and without gastrointestinal symptoms, cytology brush samples were collected during endoscopy from 316 individuals. Mucosal status was classified as normal mucosa (171), nonatrophic H. pylori gastritis (33), atrophic gastritis (12), or antral chemical gastritis (61). The 16S rRNA gene sequencing and analysis were performed to characterize the microbiota.RESULTS:Microbiota in atrophic gastritis and nonatrophic H. pylori gastritis stomachs were dysbiotic and differed from those in the normal stomach (P = 0.001). The normal stomach had the highest microbial diversity, followed by antral chemical gastritis. The atrophic gastritis and chronic H. pylori gastritis groups had the lowest diversity, a difference that was statistically significant (P = 0.01). Besides H. pylori, non-H. pylori bacteria accounted for group differences. Microbial network analysis showed that the normal group network was most highly connected, whereas the H. pylori gastritis group had the lowest connection. We found an increasing positive co-occurrence of oral bacteria in the stomach because samples deviated from the normal network, some of which were pathogens. The H. pylori-negative group had the highest microbial diversity (Shannon index) compared with the H. pylori-positive group (P = 0.001).DISCUSSION:In this low-H. pylori prevalence general population, the gastric mucosal microbiota of the normal stomach differed significantly from those with nonatrophic or atrophic gastritis. There was an increasing abundance of pathogenic bacteria from the normal state to early precancerous states.
CRIS-Team Scopus Importer:2025-03-05